Infrared Nanosecond Laser Texturing of Cu-Doped Bioresorbable Calcium Phosphate Glasses - Devanarayanan Meena Narayana Menon; Diego Pugliese; Davide Janner (Applied Sciences, 2022)
The surface modification of bioactive glasses significantly impacts their performance for in-vivo biomedical applications. An affordable nanosecond pulsed laser surface-modification technique would provide great flexibility in applications such as cell scaffolding and fouling/anti-fouling engineered surfaces. This study reports on an infrared nanosecond laser modification technique we developed and applied to a Cu-doped bioresorbable calcium phosphate glass. With this technique, clean micro-protrusion features could be produced. By tuning the laser parameters such as the laser scan speed and average power, the width and height of the formed protrusions could be controlled. Finally, optimal laser parameters were defined to obtain complex surface textures without significant damage or thermal-stress-induced cracks. These results could provide effective aid for the affordable, fast, and selective surface texturing of metal-doped bioglasses, opening new possibilities in their application in the biological field.